Flextensional ultrasonic piezoelectric micro-motor - Leinvuo, Joni T.; Wilson, Stephen A.; Whatmore, Roger W.; Cain, Markys G. (Institute of Electrical and Electronics Engineers (IEEE), 2006)
This paper presents the experimental design, construction, and operational characteristics of a new type of standing wave piezoelectric ultrasonic micro-motor. The motor uses a composite stator, consisting of a metallic flextensional mode converter, or "cymbal," bonded to a 2-mm-square piezoelectric plate. The cymbal converts contour-mode vibrations of the plate into oscillations in the cymbal, perpendicular to the stator plane. These are further converted into rotational movement in a rotor pressed against the cymbal by means of an elastic-fin friction drive to produce the required rotary actuation. The motor operates on a single-phase electrical supply, and direct control of the output speed and torque can be achieved by adjusting the amplitude and frequency of the supply voltage. Noncontact optical techniques were used to assess the performance of the developed micro-motor. The operational characteristics were developed from the acceleration and deceleration characteristics. No-load output speed (11 rev s-1) and stall torque (27 nNm) were derived using high-speed imaging and image analysis. Maximum efficiency was 0.6%